Long-term consequences of neonatal encephalopathy in the hypothermia era: protocol for a follow-up cohort study at 9 years of age - Thuy Mai Luu; Pia Wintermark; Guillaume Gilbert; Marie Brossard-Racine; Emmanouille Rampakakis; Christine Lucas Tardif; Angela White; Anne Gallagher; Elana Pinchefsky; Tina Montreuil; Marie-Noelle Simard (BMJ Open, 2023)
Introduction Therapeutic hypothermia (TH) became the standard of care treatment for neonates with moderate and severe neonatal encephalopathy (NE) in most industrialized countries about 10 years ago. Although TH is effective in reducing mortality and the incidence of severe developmental disabilities, the recent literature converges in reporting frequent cognitive and behavioural difficulties at school entry in children with NE-TH. Although these challenges are deemed minor compared with cerebral palsy and intellectual disability, their impacts on a child’s self-determination and family’s well-being are quite significant. Therefore, the nature and extent of these difficulties need to be comprehensively described so that appropriate care can be offered.Methods and analysis The current study will be the largest follow-up study of neonates with NE treated with TH to characterize their developmental outcomes and associated brain structural profiles at 9 years of age. Specifically, we will compare executive function, attention, social cognition, behaviour, anxiety, self-esteem, peer problems, brain volume, cortical features, white matter microstructure and myelination between children with NE-TH and matched peers without NE. Associations of perinatal risk factors and structural brain integrity with cognitive, behavioural and psycho-emotional deficits will be evaluated to inform about the potential aggravating and protective factors associated with function.Ethics and dissemination This study is supported by the Canadian Institute of Health Research (202203PJT-480065-CHI-CFAC-168509), and received approval from the Pediatric Ethical Review Board of the McGill University Health Center (MP-37-2023-9320). The study findings will be disseminated in scientific journals and conferences and presented to parental associations and healthcare providers to inform best practices.Trial registration number NCT05756296.